Enhanced structural and dielectric behaviour of PVDF-PLA binary polymeric blend system. (March 2021) - Mishra, Suvrajyoti; Sahoo, Rajesh; Unnikrishnan, Lakshmi; Ramadoss, Ananthakumar; Mohanty, Smita; Nayak, Sanjay Kumar
Graphical abstract: Highlights: Miscible binary PVDF-PLA blends are prepared through solvent casting using a common solvent. Improved electroactive phase content of unstretched (F (β) = 69 %) and stretched (F (β) = 75 %) PVDF-PLA blend. Improved dielectric behaviour (ε' = 14.4 and tan δ = 0.001) of mechanically stretched blends at stretch ratio 3. Enhanced structural and dielectric properties confirms successful intermolecular interaction between PVDF and PLA. Abstract: In this study, we attempted to prepare a binary polymer blend of poly (vinylidene fluoride) (PVDF) and poly lactic acid (PLA) by employing solvent casting method. Both PVDF and PLA possessing good piezoelectric properties, are considered for energy storage and energy harvesting applications. PVDF-PLA blends were uniaxially stretched at stretch ratios 1–3 to modify the structural and dielectric properties. Spectroscopic studies such as; Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis confirmed the improvement in electroactive polar phases of PVDF thus revealing the successful intermolecular interaction between CH2 and CF2 group of PVDF and -C = O or −OH or −CH3 group of PLA leading to good compatibility between both the polymers. Impedance specroscopy measurement confirmed the enhanced dielctric behaviour of unstretched (ε' = 10.5 and tan δ = 0.001) as well as mechanically stretched blend (ε' = 14.4 and tan δ = 0.001) which is ascribed to the formation of smaller spherulites at their interface which eventually facilitated their interfacial polarisation.